Biofilm Analysis of Retrieved Dental Implants after Different Peri-Implantitis Treatments - Thaise C. Geremias; Juan F. D. Montero; Ricardo de Souza Magini; Guenther Schuldt Filho; Edival Barreto de Magalhães; Marco A. Bianchini (Hindawi Limited, 2017)
The aim of the current study was to analyse the planktonic growth of Streptococcus mutans on the surfaces of three implants retrieved after three different peri-implantitis treatments. Three implants from a male patient with high levels of bone loss were treated by mechanical debridement, chemical decontamination, and implantoplasty. After 4 months of follow-up, the implants were removed. The growth and biofilm formation were measured by spectrophotometry (OD630 nm) and scanning electron microscopy (SEM), after 48 hours of incubation. Results showed an average of Streptococcus mutans planktonic growth over the implants of 0.21 nm (mechanical debridement), 0.16 nm (chemical decontamination), and 0.15 nm (implantoplasty). Data were analysed by ANOVA and Tukey's test (p<0.05 for chemical decontamination and implantoplasty). Implantoplasty and chemical decontamination showed the lowest levels of planktonic growth, indicating a possible influence of the modification procedures on the titanium surface on the initial biofilm attachment.